Green Economic Development in Developing Countries: a Systematic Literature Review and Future Research Agenda - Saputra, Priangga Eko; Muhammad, Naufal Dzakwana; Fattah, Fuad Abdul; Mala4, Iva Khoiril (PT FORMOSA CENDEKIA GLOBAL, 2024)
Global climate change is one of the major challenges of the 21st century, mainly caused by global warming which is closely related to environmental degradation. This study analyzes the implementation of green economy in developing countries during 2019-2024, focusing on trends, enablers, barriers, and contributions to SDGs. Government policies play a key role through renewable energy investment, green technology innovation, circular economy, and incentive regulation. Key barriers include limited funding, transition costs, infrastructure, and dependence on fossil fuels. A holistic approach is needed, including international collaboration, strengthening research, and adaptive policies for an inclusive transition. Green economy supports SDGs 7, 8, 9, 11, 12, and 13, accelerating sustainable development. These results underscore the importance of strong policies to achieve social, economic, and environmental sustainability.